Salus Animarum: Some Examples of the Administration of Viaticum to Plague Victims in the Post-Tridentine Period - Bradley, James E. (Studia canonica, 2021)
Times of crisis have always provided opportunities for the Church to revisit and revise her canonical and liturgical discipline, whether by permanently altering her laws, or in the temporary cessation or introduction of certain practices better suited to the particularities of the circumstances. This is no less so when such crises arise from serious sickness, and the history of the Church’s legislation governing sacramental and liturgical acts is replete with examples. In this essay, the A. considers the contributions of Saint Charles Borromeo, Saint Alphonsus Liguori, and Prospero Lambertini’s De Synodo dioecesana, particularly concerning the administration of Holy Communion to those suffering from infectious or contagious disease.